Study Social Mapping of Sorghum Farming Potential in Pohuwato District : (Case Study in Pohuwato Regency) - Tresya Daloma; Wawan K. Tolinggi; Nur Silfiah Amin (Majapahit Journal of Islamic Finance and Management, 2025)
This study aims to: 1) find out how the social mapping of sorghum farming potential in Pohuwato Regency is carried out; 2) to analyze what... factor -factor Which influence the potential of sorghum farming in Pohuwato Regency. This research was conducted in Pohuwato Regency from May to October 2025 with 8 informants. The research method used was a qualitative method with data collection techniques through observation, in-depth interviews, and documentation. The results of the study, analyzed using NVivo 12 Pro software, showed that the perception of sorghum farmers in Pohuwato Regency was generally positive, although they still face major obstacles in the form of unclear markets and selling prices. The economic potential of sorghum is considered better than that of corn if price and market problems are resolved.